Staphylococcus argenteus as an etiological agent of prosthetic hip joint infection: a case presentation - Söderquist, Bo (J Bone Jt Infect, 2020)
This report presents a case of prosthetic hip infection caused by Staphylococcus argenteus, a potentially overlooked etiology of prosthetic joint infections (PJIs). Whole-genome sequencing showed that the S. argenteus isolate was an ST2250 and clustered within other CC2250 isolates, the largest clonal group of S. argenteus. This sequence type is prevalent and may be associated with invasive infections. The present isolate was phenotypically fully susceptible to all tested antimicrobial agents and genome analysis did not detect any resistance genes, nor were any staphylococcal cassette chromosome residues detected. Despite initial appropriate management with debridement and biofilm-active antibiotics, the outcome was unfavorable with recurrence and a persistent infection treated with suppressive antibiotics. Regarding the repertoire of genomic traits for virulence in S. argenteus, PJIs caused by this bacterium should be treated accordingly as Staphylococcus aureus PJIs.